Karakteristik Nori dari Campuran Rumput Laut Ulva lactuca dan Gelidium sp.: Characteristic of Nori from Combination of Ulva lactuca and Gelidium Seaweed - Gisella Valentine; Sumardianto; Ima Wijayanti (Jurnal Pengolahan Hasil Perikanan Indonesia, 2020)
Nori is a food product produced from Phorphyra seaweed, however, this seaweed is not available in Indonesia. Thus modification of nori production by using available seaweed such as Ulva lactuca and Gelidium is needed. U. lactuca contains chlorophyll which can contribute to the nori's green color while Gelidium can become an emulsifier, stabilizer, thickener, stabilizer, purifier, and gel maker. The combination of the two seaweeds is expected to produce nori with characteristics close to commercial products. This study was aimed to examine the effect of different ratio of Ulva lactuca and Gelidium on hedonic values, tensile strength, crude fiber, protein, water, and ash content of nori. Three ratios of Ulva lactuca and Gelidium were used comprising P1 (75%: 25%), P2 (50%: 50%), and P3 (25%: 75). The ratios of U. lactuca and Gelidium significantly affected (p<0.05) sensory value (hedonic), tensile strength, crude fiber, protein and ash content, but not water content. The P1 treatment nori was preferred by the panelists with a hedonic value of 7.26<µ<7.41 and had the characteristics of dark green color, easily folded, thin, smooth texture and salty taste, similar to commercial nori. The P1 Nori had tensile strength values 4.65±1.5 MPa; crude fiber20.44±1.78%; water 17.24±0.57%, protein 12.89±0.07% and ash content 14.71±0.09%.